The Dilemma of Handling Asylum Seekers and Illegal Migrants: Expectation and Reality - Marten Hanura; Reni Windiani; Tri Cahyo Utomo (Department of International Relations, Universitas Andalas, 2021)
The number of refugees and illegal migrants fleeing to Indonesia keeps growing significantly since Indonesia poses as a strategic place for a temporary stop before their main destination. This surely brings about predicaments to Indonesia. Against that background, this research aims toanswer the question of